ARKEOLOGI KAWASAN TAPAL BATAS: KONEKSITAS KEPULAUAN MALUKU DAN PAPUA - Marlon NR Ririmasse (BALAI ARKEOLOGI PAPUA, 2011)
Maluku and Papua are two areas with the specific characters that geogaphically slocated close to each other. As an archipelagic region Maluku has a dominant maritime background while Papua shows a large and complex continent profile. The specific character as a region has made Maluku became the part of an ecological terminal between Asia and Australia known as Wallacea. Papua, which was the part of Greater Australia Continent in the past, has the similar role as a main corridor to the Pacific. This similarity has made the role of these two region is important in the study of cultural history of Southeast Asia , Australia and the Pacific Islands. This paper is a short review to observe the connecting aspects of Maluku Archipelago and Papua as a border area in the study of regional archaeology.